Fostering Students' Interest in Learning Uzbek Language in Academic Lyceums in Uzbekistan: Strategies for Success - Ismoilova Gulhayo (Zien Journals, 2024)
The Uzbek language holds immense cultural and historical significance in Uzbekistan. However, in academic lyceums, where students are exposed to a diverse range of subjects, maintaining interest in learning Uzbek language can be a challenge. This article aims to explore effective strategies to enhance students' interest in learning the Uzbek language, ensuring its preservation and promoting a deeper understanding of Uzbekistan's rich heritage
Keywords: Uzbek language; effective strategies